Assessment of oral hygiene parameters in association to eating behaviors and healthy eating self-efficacy in school-aged children - Seda Ceren Gökçek; Sabiha Ceren İlisulu (BMC Oral Health)
Abstract Background Eating behavior are a broad category influenced by a various personal, social, cultural, environmental, and economic factors. The objective of this study was to evaluate the oral hygiene status of school-aged children in relation to their eating behavior and healthy eating self-efficacy. Methods The study was carried out with the participation of 225 children aged 7–9 years. Parents carried out the Children’s Eating Behavior Questionnaire (CEBQ) to assess eating behaviors and provided sociodemographic information. Oral examinations of the children were provided according to plaque index (PI), gingival index (GI), simplified oral hygiene index (OHI-S), dmft and DMFT and, the Healthy Eating Self-Efficacy Scale (HESES) was administered to the children. For statistical analysis, a consistent partial least squares structural equation model (PLS-SEM) technique was utilized. Results A statistically significant negative correlation was found between the Healthy Eating Self-Efficacy Scale and the PI, GI, OHI-S, dmfs (p < 0.001) and DMFS (p = 0.002). Emotional undereating significantly negatively affected dmfs (p = 0.021), while emotional overeating had a significant positive effect on DMFS (p = 0.036). None of the eating behavior subgroups in children showed a significant relationship with self-efficacy. Additionally, higher self-efficacy (p = 0.001) and food fussiness (p = 0.001) were found in children from high-income families, while emotional overeating (p < 0.001) and desire to drink (p = 0.009) were observed in children from middle-income families. Conclusion This study reveals a significant relationship between healthy eating self-efficacy and oral hygiene in children. Higher self-efficacy correlates with better oral health, while emotional eating negatively impacts dental outcomes. Socioeconomic factors also play a role, suggesting that interventions should target self-efficacy and emotional eating to improve both eating behaviors and oral health in school-aged children.